Citizen and Pariah (African Human Mobility Review, 2022)
Citizen and Pariah is the title of a book by Vanya Gastrow that is based on her doctoral and postdoctoral research. In the preface Gastrow informs the reader that “the book investigates violent crime affecting Somali shopkeepers, their ability to access informal and formal justice mechanisms, and efforts to regulate their economic activities”.